An Analysis of the Types and Functions of EFL Teacher’s Classroom Language as Used at 7th-Grade Junior High School 13 of Mataram - Windilia Eo Manurak; Sudirman Wilian; Amrullah; Lalu Nurtaat (Journal of English Education Forum (JEEF), 2026)
This study aims to investigate the types, functions, and language distribution of classroom language used by Grade VII English teachers at SMPN 13 Mataram. Employing a qualitative case study design, data were collected through non-participant observations, audio-video recordings, and semi-structured interviews with two teachers. The analysis followed Miles and Huberman’s interactive model. Findings reveal that teachers employed two major types of classroom language based on Hughes’ framework: instructional talk (49.8%) and managerial talk (50.2%). Instructional talk encompassed explaining, questioning, eliciting, checking understanding, giving feedback, and directing students, while managerial talk included opening routines, giving instructions and directions, praise, attendance checking, attention getters, and other regulatory expressions. In terms of function, classroom language predominantly served pedagogical purposes (78%), particularly instructional-managerial and language modelling functions, with social functions accounting for 22%. Regarding language choice, Indonesian was most dominant (43%), followed by English (34%) and mixed code-switching (21%), especially during core instructional activities to ensure comprehensible input. English was mainly used for routines, simple instructions, and modeling. The findings indicate that teachers strategically balance first language support and target language exposure to facilitate comprehension and participation. Future research should examine the longitudinal impact of classroom language patterns on students’ speaking proficiency and communicative competence.